Neutralization Of The National Police In The General Election In Maintaining The Collapse Of The Unitary State Of The Republic Of Indonesia - Hasibuan, Edi Sahputra (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The glue in democracy, especially in the run-up to the 2024 elections, is a stronger civilian authority accompanied by optimal parliamentary oversight, and the creation of professional security actors (military and police). "Professional" means the military (and police) are not involved or involved in politics. These two things are the main indicators in seeing how the quality of democratic consolidation. Moreover, the professionalism of security actors is in line with the democratic system of government. But in the context of Indonesia, one of the challenges of all-digital democracy is the effort to create professionalism of security actors so that they are involved in the political frame; or commonly called TNI/Polri neutrality. This paper will analyze specifically the neutrality of the National Police in the 2024 election process. There are two considerations to this review. First, because the National Police carries out security and public order functions in the community; including in this case maintaining the security of the 2024 election. Second, because the National Police also has a preventive function to prevent security disturbances, especially before the election. In general, this function is carried out by every member of the National Police, but specifically the preventive function in the form of detection of potential security disturbances at the village level is attached to Babinkamtibmas members.